Treatment outcome of TB patients in a district of north India: a three year study - Padda, P; Gupta, V; Devgan, S; Chaudhary, S; Singh, G (Nepal Journal of Epidemiology, 2015)
Background Tuberculosis (TB), still remains a public health problem of great concern. It was estimated that 8.6 million people developed TB and 1.3 million died from it. India has the highest TB burden in the world. DOTS ensures high cure. Therefore the present study was planned to assess the outcome of DOTS treatment among pulmonary and extra pulmonary TB patients reporting at DOTS centers of the district Materials and methods: A record based study using the routine program data of Revised National Tuberculosis Control Programme was conducted in one of twenty two districts of state of Punjab, situated in northern India. Records of all the patients registered from 1st January 2011 till 31st December 2013 were analysed using descriptive statistics. The differences between proportions were compared using tests of significance. Results: A total of 2571 new cases of Tuberculosis were registered during the study period of three years, out of which 44.8%, 22.9% and 32.3% were diagnosed to be new smear positive, smear negative and suffering from Extra pulmonary tuberculosis (EPTB) and a total of 369 retreatment cases were registered. Cure rates were highest among patients suffering from EPTB when compared to those of smear positive and smear negative. The proportion of defaulters among smear positive failures was highest, followed by smear positive after default and lowest in smear positive relapses. Conclusion Cure rates were higher among EPTB cases whereas default rate was more among patients suffering from pulmonary TB. Therefore higher level of motivation of cases by health and non-health personnel is required as untreated or under treated pulmonary TB cases are responsible for transmission of the disease in the community. Default rates could be decreased by concrete efforts in the form of strict supervision and monitoring. DOI: http://dx.doi.org/10.3126/nje.v5i1.12376